Kinerja Implementasi Pelayanan Publik Pemerintah Kecamatan di Kota Cilegon - Ahmad Sururi (Universitas Muhammadiyah Ponorogo, 2020)
The purpose of this paper is to analyze how the performance of the implementation of district government services in the city of Cilegon. To measure the performance of policy implementation, the authors use two indicators namely first, the policy output indicator consisting of coverage, bias, access, frequency and service delivery as well as the suitability of the program to the needs, second, indicators of policy impact namely initial impact, medium impact and long term impact. The research method used is a qualitative approach with primary data collection techniques and secondary data, the research locus is in Cibeber District, Cilegon City. Based on measurements that the performance of the implementation of public service policies in public sector organizations Cibeber District Cilegon City has been running effectively. This can be seen from the policy output indicators consisting of coverage, bias, access, frequency, service delivery and program suitability with the need to show effective indicators even though the indicators of access to participation in policy/program socialization activities, mechanisms, procedures and procedures of the public get service. While the impact of service policy based on the initial impact, medium-term impact and long-term impact shows the performance of the implementation of service policy has been running effectively and in accordance with the vision and mission of Cibeber District, Cilegon City.